2020
DOI: 10.3390/ijms21051782
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Network between MYC Oncogene and microRNAs in Gastric Cancer: An Overview

Abstract: Despite the advancements in cancer treatments, gastric cancer is still one of the leading causes of death worldwide. In this context, it is of great interest to discover new and more effective ways of treating this disease. Accumulated evidences have demonstrated the amplification of 8q24.21 region in gastric tumors. Furthermore, this is the region where the widely known MYC oncogene and different microRNAs are located. MYC deregulation is key in tumorigenesis in various types of tissues, once it is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 143 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…Aberrant expression of c-Myc leads to genomic instability and tumorigenesis and maintains tumor growth [ 48 ]. One study found that the mRNA and protein expression of c-Myc were increased in HGC-27 and SGC-7901 gastric cancer cell lines compared with the human gastric mucosal cell line GES-1, and knockdown of c-Myc expression inhibited gastric cancer cell proliferation [ 49 ]. Therefore, the silkworm carboxypeptidase inhibitor likely down-regulated the expression of c-Myc, leading to an inhibited proliferation of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of c-Myc leads to genomic instability and tumorigenesis and maintains tumor growth [ 48 ]. One study found that the mRNA and protein expression of c-Myc were increased in HGC-27 and SGC-7901 gastric cancer cell lines compared with the human gastric mucosal cell line GES-1, and knockdown of c-Myc expression inhibited gastric cancer cell proliferation [ 49 ]. Therefore, the silkworm carboxypeptidase inhibitor likely down-regulated the expression of c-Myc, leading to an inhibited proliferation of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The Bcl-2 family, on the other hand, is part of the core mechanism of apoptosis, and the anti-apoptotic properties of Bcl-2 protect cells from various damaging factors ( Schenk et al, 2017 ). The myc gene family mainly comprises C-myc, N-myc, and L-myc—three highly related nuclear phosphorylated proteins, and the literature suggests that activation of the myc genes may affect cell function, inhibit apoptosis, promote abnormal cell proliferation, and lead to tumorigenesis through multiple pathways ( Ba et al, 2018 ; Tong-peng et al, 2019 ; Anauate et al, 2020 ). c-myc genes are indicators for the evaluation of the effect of the GC disease process and treatment, and therefore, they are the most frequently studied indicators in studies on GC ( Won et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As we all have known TF, MYC promotes the progression of STAD through regulating downstream genes and different pathways. 21 FOXM1 has also been testified to play a crucial role in the occurrence and chemoresistance of gastric cancer. 22 As the potential targets of TFs, RBPs and their roles in STAD deserve our further efforts.…”
Section: Discussionmentioning
confidence: 99%